1984
DOI: 10.1136/thx.39.10.798
|View full text |Cite
|
Sign up to set email alerts
|

Primary angiosarcoma of the heart mimicking a left atrial myxoma.

Abstract: Sarcomas as a group are the second most common type of primary tumour of the heart.' Angiosarcoma is, however, an unusual form of tumour within this group and is rarely diagnosed during life.2 It is almost exclusively a tumour of the right atrium and pericardium, patients presenting with symptoms of right heart inflow obstruction and pericardial disease.3 We present here a case of primary angiosarcoma of the heart causing obstruction of the mitral valve. Two dimensional echocardiography suggested the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…A similar experi ence was reported by Ormerod et al [11], Sorbe et al [13], Hammond et al [14], Winer et al [15], Shah et al [16], Olds et al [20], and Nzayinambaho et al [22] who all observed predunculated primary cardiac sarcomas (angiosarcoma, chondrosarcoma, osteosarcoma, fibrous histiocytoma, mesothelioma, liposarcoma) initially thought to be atrial myxomas (left or right) by clinicoechocardiographic examination. Rosman et al [23] have reported right and left atrial nonprolapsing rhabdomyosarcomas, and Schmaltz and Apitz [21] described a primary rhabdomyosarcoma in the pediatric age group.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…A similar experi ence was reported by Ormerod et al [11], Sorbe et al [13], Hammond et al [14], Winer et al [15], Shah et al [16], Olds et al [20], and Nzayinambaho et al [22] who all observed predunculated primary cardiac sarcomas (angiosarcoma, chondrosarcoma, osteosarcoma, fibrous histiocytoma, mesothelioma, liposarcoma) initially thought to be atrial myxomas (left or right) by clinicoechocardiographic examination. Rosman et al [23] have reported right and left atrial nonprolapsing rhabdomyosarcomas, and Schmaltz and Apitz [21] described a primary rhabdomyosarcoma in the pediatric age group.…”
supporting
confidence: 53%
“…The presence of pericar dial effusion may be a clue to the diagnosis of malignan cy. Metastatic lesions on the surface of the heart may be observed and tumor infiltration of the heart walls visual ized; however, the extent of intramural growth may not be recognized or heavily underestimated by 2D, particu larly when the images are less than optimal [8,11]. Mich et al [19] stressed the significance of tumor extension into pulmonary veins and an unusual site of tumor ori gin as significant clues to the diagnosis of malignancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a literature review through PUBMED from 1980 to 2008, more than 250 cases of cardiac angiosarcoma were found; the tumors mostly arose from the right atrium with different extensions and clinical presentations. In the last two decades, only eight cases of this malignant tumor originating from LA were reported in the English literature 1‐8 . This present report describes the ninth case of primary cardiac angiosarcoma arising from an extremely unusual location.…”
Section: Discussionmentioning
confidence: 78%
“…8 However, we are the first to describe a severe functional mitral valve obstruction caused by a cardiac angiosarcoma. In this case, echocardiography was extremely helpful in describing the morphology, size, and origin of the cardiac mass ( fig 1).…”
Section: Discussionmentioning
confidence: 98%